INFLUENCE OF CIRCULAR EXERCISES ON THE CARDIOVASCULAR AND RESPIRATORY SYSTEM OF FEMALE STUDENTS - P. Petkov (Trakia Journal of Sciences)
The purpose of the present study is to determine the influence of circular exercises on the cardiovascular and respiratory systems of Trakia's University female students. To achieve this goal the following methods are used: testing, pedagogical experiment, variation analysis, comparative analysis, graphic analysis. 69 female students are the contingent of the study with an average age of 20.04 years old from the first and second school year, studying in three different faculties of the Trakia University - Faculty of Economics, Faculty of Agriculture and Faculty of Veterinary Medicine. They were divided into two groups. The experimental group of 36 female students - with this group was hold circuit trainings twice a week in the duration of 30 weeks. On the basis of the conducted research, in order to increase the efficiency of the fitness training by applying a specialized training fitness model intended for the students, and the analyzes made it can be concluded: The effectiveness of the author's fitness model, based on circular training, as part of the overall fitness training of the students for strengthening the cardiovascular and the respiratory systems of the students, are experimentally substantiated.